Event Oriented Representation for Collaborative Activities (EORCA) - Pellegrin, L.; Bonnardel, N.; Antonini, F.; Albanese, J.; Martin, C.; Chaudet, H. (Methods of Information in Medicine, 2007)
Objectives: In this paper, we introduce a method that aims at describing components of medical activities that are performed by a medical team, including physicians and nurses, during patients’ management in an ICU (intensive care unit). This method is based on formal taskanalyses developed in cognitive ergonomics.Our ultimate aim is to build a method covering the observation and the representation of collective activities during patients’ management, which should be re-usable by the team members in order to prepare themselvesfor accreditation.Methods: This method comprises two main steps: – the formal observations of medical staff’s activities that occur during patient management, -a representation of the findings with regard to an ontology and a temporal flowchart, which describes actors and events related to patient management.Results: This paper describes field studies performed in ICUs. This method has been used for analyzing the management of 24 cases of neurological and multiple traumas. We have represented the different actions of the medical team members (clinicians, nurses and outside medical consultants).Conclusion: The results allow us to identify the specific features of these complexand time-constrained situations, especially about the strong collaborative activities between members of the patient-care teams, especially the interaction between information management and medical actions.
Keywords: Medical decision-making; collaborative work; task performance and analysis; intensive care unit